Upaya Unit Pelaksanaan Teknis Daerah (UPTD) Kesejahteraan Sosial Anak Riang Dalam Meningkatkan Kecakapan Hidup Anak Melalui Program Pertanian Di Kelurahan Naibonat Kecamatan Kupang Timur Kabupaten Kupang - Leu, Maria Redigundis; Sogen, Yosephina K; Mardani, Ambara Saraswati (Education For All, 2025)
This research is motivated by the agricultural program implemented by the UPTD Social Welfare of Riang Children, has been hampered due to limited funds and the consequences of the Covid-19 outbreak. Therefore, efforts are made to keep children participating in the program, even though there are still obstacles. Descriptive qualitative research method with a case study approach. The location of the research was at the Technical Implementation Unit (UPTD) of Social Welfare of Riang Children in Naibonat Village, East Kupang District, Kupang Regency. The subjects of the study are Heads, Employees, Agricultural Instructors and Beneficiary Children. Data collection uses interview, observation and documentation techniques. Then a data validity test and data analysis were carried out. The results of the study showed four classifications of Life Skills (1) Personal Skills, children choose programs that are of interest and are able to understand them after practice. (2) Social Skills, lack of interaction, so that the instructor divides the children into several groups and is given socialization. (3) Academic Skills, the instructor does not prepare modules or syllabus and there is no assessment, only general explanation. (4) Vocational Skills, various types of vegetables and corn are planted so that children are able to understand how to plant, take care of plants until harvest and sell the results.